Formulasi Tepung Ubi Ungu dan Tepung Ikan Gabus sebagai Snack Pemberian Makanan Tambahan Balita: Formulation of Purple Sweet Potato Flour and Snakehead Fish Flour as a Supplementary Feeding Snack for Toddlers - Sari Oktaviana; Eko Basuki; Siska Cicilia (Jurnal Teknologi dan Mutu Pangan, 2026)
Purple sweet potato flour has a high carbohydrate content, making it a good source of carbohydrates in food products. However, purple sweet potatoes are low in protein, so other protein sources are needed, primarily animal protein such as snakehead fish. This study aims to determine the formulation of purple sweet potato flour and snakehead fish flour as snacks for toddlers. This study used an experimental method with a completely randomized design (CRD) of 1 factor and 6 treatments with 3 repetitions to compare the formulations of purple sweet potato flour and snakehead fish flour, namely P0 (100%:0%), P1 (95%:5%), P2 (90%:10%), P3 (85%:15%), P4 (80%:20%), and P5 (75%:25%). The parameters observed were chemical quality (moisture content, ash, protein, fat, carbohydrates, and calories) and organoleptic quality (aroma, taste, color, and texture). The results showed that the formulation of purple sweet potato flour and snakehead fish flour had a significant effect on chemical and organoleptic quality in each treatment. The best treatment was obtained in the P4 formulation of 80% purple sweet potato flour and 20% snakehead fish flour, which contained 188.59 kcal of energy, 5.01% protein, and 8.74% fat with organoleptic quality preferred by panelists, having a distinctive snakehead fish aroma, slightly bitter, light brown color, and crispy texture. Thus, it is hoped that this study will serve as a basis for developing PMT products for malnourished toddlers.